PENGARUH FUMIGASI AMONIUM HIDROKSIDA TERHADAP EMISI FORMALDEHIDA KAYU LAPIS DAN PAPAN PARTIKEL - Adi Santoso; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 2004)
The formaldehyde emmision of panel products such as plywood and particleboard bonded with urea formaldehyde (UF) may affect health, especially when they are used in a room with poor ventilation. To reduce formaldehyde emission, the products can be fumigated by a chemical agent. This paper described the effect of fumigation by ammonium hydroxide 25% on formaldehyde emission of UF bonded plywood and particleboard.The effect of fumigation by ammonium hydroxide on formaldehyde emission of plywood and particleboard are higly significant. The longer the fumigation by ammonium hydroxide, the lower the formaldehyde emission of plywod and particleboard. Fumigation by ammonium hydroxide of 1 hour and 1. 5 hours, the formaldehyde emission of plywood and particleboard can meet Japanese Standard on the mean value of 0.632 mg/I and 0.349 mg/I for plywood, and 4.594 mg/l and 2.225 mg/l for particleboard. Meanwhile, fumigation on particleboard of 1. 5 hours and on plywood of all treatment 0.5 to 1.5 hours, the formaldehyde emission can conform with American Standard on the mean value of 0.261 mg/l for particleboard and 0.154 to 0.042 mg/I for plywood. On the basis of formaldehyde emission standards, it is recomended than the fumigation by ammmonium hydroxide 25% may be used in plywood for 70 minutes and on particleboard for 80 minutes.